Analyzing the Intrinsic Motivation of the Main Character in the Movie Joy - Rahmani, Eka Fajar; Empawi, Aprianus Agung; Sada, Clarry (LPPM Universitas Bumigora Mataram, 2024)
The film Joy is a motivational movie that inspires viewers to work hard and achieve their dreams. This research examines the intrinsic motivation of the main character based on the Basic Psychological Needs Theory, which suggests that intrinsic motivation is driven by three core psychological needs: autonomy, competence, and relatedness. The study explores how these needs are reflected in the character’s actions and dialogue. Using a descriptive-qualitative method, the movie script is analyzed as a primary data source, using document analysis techniques. Data were collected through an observation table and interpreted through content analysis. The findings reveal that the protagonist’s intrinsic motivation is primarily fueled by the need for competence, as shown in seven key moments where she strives for mastery. Autonomy is also significant, seen in six instances where the character resists external pressures to assert control over her choices. Relatedness, identified in five moments, provides emotional support that sustains her motivation. These results highlight the importance of competence in driving personal achievement, while autonomy and relatedness offer essential support. The study shows how films like Joy depict psychological needs and suggests that such portrayals can inspire viewers to pursue their own goals by fostering autonomy, competence, and meaningful relationships.